2020
DOI: 10.1038/s41467-020-20002-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure of voltage-modulated sodium-selective NALCN-FAM155A channel complex

Abstract: Resting membrane potential determines the excitability of the cell and is essential for the cellular electrical activities. The NALCN channel mediates sodium leak currents, which positively adjust resting membrane potential towards depolarization. The NALCN channel is involved in several neurological processes and has been implicated in a spectrum of neurodevelopmental diseases. Here, we report the cryo-EM structure of rat NALCN and mouse FAM155A complex to 2.7 Å resolution. The structure reveals detailed inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…The structure of the NALCN-FAM155A subcomplex is overall similar to our previous structure at 2.65 Å (Fig. 1b-f) 15 . The UNC79-UNC80 heterodimer forms a large helix-rich structure in the cytosol.…”
Section: S2 S3 and Tablesupporting
confidence: 85%
See 3 more Smart Citations
“…The structure of the NALCN-FAM155A subcomplex is overall similar to our previous structure at 2.65 Å (Fig. 1b-f) 15 . The UNC79-UNC80 heterodimer forms a large helix-rich structure in the cytosol.…”
Section: S2 S3 and Tablesupporting
confidence: 85%
“…Guided by our previous high resolution structure of NALCN-FAM155A subcomplex 15 , we found that the combination of I753A, L754A, R761A, R764A and R765A mutations (CIH-5A) is sufficient to disrupt such interaction, shown by GST pull-down assay (Fig. 5f).…”
Section: Mechanism Of Nalcn Channel Regulation By Unc79-unc80mentioning
confidence: 62%
See 2 more Smart Citations
“…specifying four output classes. The best class with 245,031 particles was selected, then subjected to a resolution-based classification workflow similar to a previous study (Kang et al, 2020). In brief, 40 iterations of global search 3D classification (K=1) in Relion 3.1 with an angular sampling step of 7.5° was performed to determine the initial alignment parameters using the initial model generated from cryoSPARC.…”
Section: Image Processingmentioning
confidence: 99%